Efeitos terapêuticos da suplementação de L-arginina nas doenças cardiovasculares e endócrino-metabólicas - Puga, Guilherme Morais [UNESP]; Novais, Iane de Paiva [UNESP]; Zanesco, Angelina [UNESP] (My University, 2011)
Nitric oxide is synthesized from L-arginine and plays an important role in blood pressure regulation, platelets aggregation and atherosclerosis development. Most of the studies have shown that the beneficial effects of the L-arginine supplementation are related to an increasing of nitric oxide bioavailability to the cells, improving the endothelial dysfunction, decreasing oxidative stress, ameliorating lipid profile and insulin resistance. However some studies show conflicting results. Considering the role of the endothelium on the pathogenesis of the cardiovascular diseases as well as on the endocrine-metabolic diseases, this review will update studies involving the role of nitric oxide and its signaling pathways in the regulation of vascular function. Furthermore, this review will focus on the main results of the clinical trials using oral L-arginine supplementation, with or without physical exercise, in an attempt to obtain beneficial effects on the cardiovascular and endocrine-metabolic systems in patients and healthy subjects.
Therapeutic effects of L-arginine supplementation on the cardiovascular and endocrine -metabolic diseases
Keywords: Atherosclerosis; Cardiovascular diseases; L-arginine; Nitric oxide; arginine; nitric oxide; atherosclerosis; bioavailability; blood pressure regulation; cardiovascular disease; endocrine disease; endothelial dysfunction; exercise; human; insulin resistance; lipid analysis; metabolic disorder; oxidative stress; protein analysis; protein function; review; thrombocyte aggregation